2005
DOI: 10.1007/s10384-005-0210-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of the Novel Na+/Ca2+ Channel Blocker NS-7 on Rat Retinal Ganglion Cells

Abstract: NS-7 has neuroprotective effects against retinal damage resulting from subjection to ischemia. In addition, NS-7 can be used as an agent for treating acute ischemic retinopathy, including diseases associated with very high intraocular pressure, such as acute angle-closure glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…22 This potential neuroprotective effect of flunarizine has been studied in a variety of experimental models, including ischemia-reperfusion models in rabbits, 3 rats, 33 sheep, 17 and gerbils 21 ; in sciatic 20 and optic 19 nerve axotomy in rats; and in a model of light-mediated injury to the rat retina. 18 Calcium antagonists have also been reported to be neuroprotective in ischemia-reperfusion models in vivo 34,35 and in excitotoxicity models in which retinal ganglion cells and cortical neurons in cell culture were exposed to N-methyl-D-aspartate and glutamate 3,35 or in which nerve growth factor was withdrawn. 20 In addition, the effect of this class of agents on vascular smooth muscle could contribute to the improvement in optic nerve head or retinal blood flow measured in normal subjects and in patients with glaucoma after treatment with calcium channel blockers, 9,15,16,28 and to the improvement in visual field parameters observed in patients with normal tension glaucoma.…”
Section: Discussionmentioning
confidence: 98%
“…22 This potential neuroprotective effect of flunarizine has been studied in a variety of experimental models, including ischemia-reperfusion models in rabbits, 3 rats, 33 sheep, 17 and gerbils 21 ; in sciatic 20 and optic 19 nerve axotomy in rats; and in a model of light-mediated injury to the rat retina. 18 Calcium antagonists have also been reported to be neuroprotective in ischemia-reperfusion models in vivo 34,35 and in excitotoxicity models in which retinal ganglion cells and cortical neurons in cell culture were exposed to N-methyl-D-aspartate and glutamate 3,35 or in which nerve growth factor was withdrawn. 20 In addition, the effect of this class of agents on vascular smooth muscle could contribute to the improvement in optic nerve head or retinal blood flow measured in normal subjects and in patients with glaucoma after treatment with calcium channel blockers, 9,15,16,28 and to the improvement in visual field parameters observed in patients with normal tension glaucoma.…”
Section: Discussionmentioning
confidence: 98%
“…The study showed that orally delivered phenytoin was effective in protecting neurons. Saito et al investigated whether NS-7 (4-(4-fluorophenyl)-2-methyl-6-(5-piperidinopentyloxy) pyrimidine hydrochloride [ 55 ], a novel Na + /Ca 2+ channel blocker, can protect the rat retina. They showed that NS-7 has neuroprotective effects against retinal damage resulting from subjection to ischemia.…”
Section: Trace Elements In Glaucomamentioning
confidence: 99%
“…[6] The thickness of twelve areas of each retinal specimen was measured beginning from the optic disc in the center and moving peripherally in increments of 250 µm in 2 opposite ways, dorsally and ventrally, which included central and peripheral retina. The average measured values of the IPL/ONL ratio from twelve measurements of each eye were used to evaluate the extent of ischemia-reperfusion damage of retina [25].…”
Section: Histopathologymentioning
confidence: 99%